2023
DOI: 10.3390/antiox12071434
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Photodynamic Therapy Induced Bystander and Abscopal Effects: A Review

Abstract: Photodynamic therapy (PDT) is a clinically approved minimally/non-invasive treatment modality that has been used to treat various conditions, including cancer. The bystander and abscopal effects are two well-documented significant reactions involved in imparting long-term systemic effects in the field of radiobiology. The PDT-induced generation of reactive oxygen and nitrogen species and immune responses is majorly involved in eliciting the bystander and abscopal effects. However, the results in this regard ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 105 publications
0
1
0
Order By: Relevance
“…For in vitro studies on cell culture plates, recent observations have indicated that non-irradiated wells, on occasion, exhibit similar responses to irradiated ones, particularly when in close proximity (continuous well) [ 37 , 38 , 39 ]. Nevertheless, this phenomenon was described in the 1970s when elucidating photoirradiation systems for PDT in studies on cancer cells [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…For in vitro studies on cell culture plates, recent observations have indicated that non-irradiated wells, on occasion, exhibit similar responses to irradiated ones, particularly when in close proximity (continuous well) [ 37 , 38 , 39 ]. Nevertheless, this phenomenon was described in the 1970s when elucidating photoirradiation systems for PDT in studies on cancer cells [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring the long-term safety and outcomes of PDT is essential for ethical practice. Understanding the potential for delayed side effects or adverse events requires ongoing surveillance and reporting [214]. Clinicians have an ethical obligation to contribute to the body of knowledge regarding the safety profile of PDT, fostering transparency and accountability in the medical community.…”
Section: Ethical Considerations In the Use Of Photodynamic Therapymentioning
confidence: 99%
“…Photodynamic therapy (PDT) is a non-invasive treatment option for lung cancer that uses a photosensitizing agent and a specific wavelength of light to destroy cancer cells. 7,8 In PDT, reactive oxygen species (ROS) play a crucial role in the destruction of cancer cells. When photosensitizer (PS) agents are exposed to specific wavelengths of light, the PS becomes activated and transitions to a higher energy state.…”
Section: Introductionmentioning
confidence: 99%